Inhibitory effect of napabucasin on arbidol metabolism and its mechanism research - Nie, Jingjing; Xia, Hailun; Liu, Ya-Nan; Yu, Yige; Xu, Ren-Ai (Frontiers in Pharmacology, 2023)
As a broad-spectrum antiviral, and especially as a popular drug for coronavirus disease 2019 (COVID-19) today, arbidol often involves drug-drug interactions (DDI) when treating critical patients. This study established a rapid and effective ultraperformance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) to detect arbidol and its metabolite arbidol sulfoxide (M6-1) levels in vivo and in vitro. In this study, the 200 μL incubation system was used to study the inhibitory effect of the antitumor drug napabucasin on arbidol in vitro, with IC50 values of 2.25, 3.91 and 67.79 μM in rat liver microsomes (RLM) and human liver microsomes (HLM), CYP3A4.1, respectively. In addition, we found that the mechanism of inhibition was noncompetitive inhibition in RLM and mixed inhibition in HLM. In pharmacokinetic experiments, it was observed that after gavage administration of 48 mg/kg napabucasin and 20 mg/kg arbidol, napabucasin inhibited the metabolism of arbidol in vivo and significantly changed the pharmacokinetic parameters of arbidol in rats such as AUC(0t) and AUC(0-∞). We also found that napabucasin increased the AUC(0-t) and AUC(0-∞) of the main metabolite of arbidol, M6-1. This study provides a reference for the combined use of napabucasin and arbidol in clinical practice.